Citološke in biopsijske tehnike ter kolposkopija v ginekologiji - Smrkolj, Špela (Medicinski razgledi, 2011)
In order to make a diagnosis in a patieni with a gynccologic disease, detailedhistory taking and clinical examination are the firststeps to patient management, while cytological diagnostic methods (including cervical smear), colposcopy, and biopsy iechniqucs established in gynecology come next. Cervical smear scrcening is one of the most successful screening tests used inmedicine.
Keywords: Genital Diseases, Female; Ginekološke bolezni; Diagnosis; Biopsija; Pathology; Vaginalni razmazi; Kolposkopija; Biopsy; ginekologija; Vaginal Smears; citološka diagnostika; Colposcopy; diagnostika